The future of Swiss hydropower realities, options and open questions - Michael Barry; Regina Betz; Sandro Fuchs; Ludovic Gaudard; Thomas Geissmann; Gianluca Giuliani; Werner Hediger; Marc Herter; Mirjam Kosch; Franco Romerio; Moritz Schillinger; Lutz E. Schlange; et al. (University of Basel, Center of Business and Economics (WWZ), 2019)
The NRP70 project "The Future of Swiss Hydropower: An Integrated Economic Assessment of Chances, Threats and Solutions" (HP Future) has been initiated in 2014 with the objective to identify options for Swiss hydropower (HP) to adopt to the ongoing and expected electricity system changes. The project has been finalized in 2018 and this final report provides an overview of the obtained results and insights. Following a short summary of the main findings is provided.
Keywords: 330; Wasserkraftwerk; Wettbewerb; Investitionsentscheidung; Wasserpreis; Räumliche Wirkung; Nachhaltige Entwicklung; Schweiz